Entropy in regional analysis - Czyż, Teresa; Hauke, Jan (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2015)
Entropy has been proposed as a significant tool for an analysis of spatial differences. Using Semple and Gauthier’s (1972) transformation of the Shannon entropy statistic into an entropy measure of inequality and their algorithm, an estimation is made of changes in regional inequality in Poland over the years 2005–2012. The inequality is decomposed into total, inter- and intra-regional types, and an analysis is made of relations holding between them.
Keywords: entropy measure of inequality; decomposition of regional inequalities; changes in regional inequality pattern; Poland